1997
DOI: 10.3168/jds.s0022-0302(97)76302-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Mobile Computerized Grain Feeder for Lactating Cows Grazing Grass Pasture

Abstract: The objective of this study was to evaluate a mobile computerized grain feeder for use to feed individually Holstein cows grazing grass pasture. Thirty-two Holstein cows averaging 95 d of lactation and 39.3 kg/d of milk were rotationally grazed on predominantly Dactylis glomerata pastures for 9 wk starting in early May. Cows were blocked according to parity, days of lactation, and milk yield. Cows were randomly assigned to a control group in which cows were individually fed grain twice daily at milking or to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 28 publications
(40 reference statements)
1
7
0
Order By: Relevance
“…Published responses to increased concentrate feeding frequency have yielded conflicting results, with Dalley (1998) reporting improvements, but no benefits were measured by Peyraud and Delaby (2001) or Hongerholt et al (1997). Hongerholt et al (1997) did not focus on maximizing pasture intake and a concentrate-based ration was available every 6 h, whereas Dalley (1998) offered concentrate at milking and 2 h after milking, at a time when most cows had completed grazing.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Published responses to increased concentrate feeding frequency have yielded conflicting results, with Dalley (1998) reporting improvements, but no benefits were measured by Peyraud and Delaby (2001) or Hongerholt et al (1997). Hongerholt et al (1997) did not focus on maximizing pasture intake and a concentrate-based ration was available every 6 h, whereas Dalley (1998) offered concentrate at milking and 2 h after milking, at a time when most cows had completed grazing.…”
Section: Discussionmentioning
confidence: 94%
“…Hongerholt et al (1997) did not focus on maximizing pasture intake and a concentrate-based ration was available every 6 h, whereas Dalley (1998) offered concentrate at milking and 2 h after milking, at a time when most cows had completed grazing. The feeding regimen chosen by Dalley (1998) was designed to achieve some synchrony between nutrient supply from pasture and grain, with a 2.1 L response in milk production.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Grazing has several advantages with the most frequently cited ones including benefits for animal health (Burow et al, 2011) and for the environment (Peyraud and Delagarde, 2013) which are positively perceived by the consumers (De Olde et al, 2016). Including grazed pasture in cows' diet lowers milk production costs (Hongerholt et al, 1997;Dillon et al, 2005) in comparison with barn feeding, and increases the ratio of polyunsaturated fatty acids in cows' milk (Stockdale et al, 2003;Wales et al, 2009). Despite these advantages, combining grazing and AMS remains a challenge due to the lower milking frequency observed when cows are grazing (van Dooren et al, 2002;Spörndly and Wredle, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Although the system was not efficient enough to run without additional electrical power, Gardner et al (1995) concluded that photovoltaics could power such a feeder if redesigned for higher efficiency. Hongerholt et al (1997) used this system and showed that a mobile, computer-controlled concentrate feeder can successfully feed dairy cattle in a rotational grazing system. They found that the computer-controlled feeder led to less grain consumption with similar fat-corrected milk production.…”
mentioning
confidence: 99%